PsycEXTRA Dataset 2012
DOI: 10.1037/e502102013-070
|View full text |Cite
|
Sign up to set email alerts
|

Working with tacit knowledge: An empirical investigation in glass blowing tradition in Sweden

Abstract: Tacit knowledge is argued to be a crucial resource to organizations' competitive advantage. The majority of research on tacit knowledge is oriented towards the conversion of tacit knowledge into explicit knowledge, thus assuming that all knowledge can be made explicit and captured in formal ways. These approaches overlook the intangible nature of tacit knowledge by overestimating that explicit knowledge. This study takes a human centered approach with the aim to examine the factors that are necessary for an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(90 reference statements)
1
2
0
Order By: Relevance
“…Like some previous studies (Jacob and Ebrahimpur 2001; Kurti, 2011; Olsson and Gullberg, 1988), time was found from the interviews a factor influencing tacit knowledge transfer. With Kurti (2011) and Olsson and Gullberg (1988) positing that tacit knowledge transfer requires apprentices spending a prolonged time with their masters, the study supported this; a few participants attested that the amount of time to share all their skills and expertise in a working environment was limited as new styles pop up often. This means that for a successful transfer of tacit knowledge, apprentice requires more time with the master.…”
Section: Discussion Of Findingssupporting
confidence: 62%
See 2 more Smart Citations
“…Like some previous studies (Jacob and Ebrahimpur 2001; Kurti, 2011; Olsson and Gullberg, 1988), time was found from the interviews a factor influencing tacit knowledge transfer. With Kurti (2011) and Olsson and Gullberg (1988) positing that tacit knowledge transfer requires apprentices spending a prolonged time with their masters, the study supported this; a few participants attested that the amount of time to share all their skills and expertise in a working environment was limited as new styles pop up often. This means that for a successful transfer of tacit knowledge, apprentice requires more time with the master.…”
Section: Discussion Of Findingssupporting
confidence: 62%
“…The apprentices surrender to the authority of the master, and by watching him/her, the apprentice captures the rules, even those that are not known to the master himself/herself (Polanyi, 1967). In the case of master/apprentice tradition, Kurti (2011) posits that it requires apprentices spending a prolonged time with their masters. Polanyi (1967) and Olsson and Gullberg (1988) share the same perspective that tacit knowledge is typically acquired through a long tradition and experience; learning tacit knowledge is a long process that involves spending a significant amount of time along the master in a working environment that mainly involves tacit knowledge.…”
Section: Factors Influencing Tacit Knowledge Transfermentioning
confidence: 99%
See 1 more Smart Citation